Exploring the use of the Flipped Classroom as an Education Delivery Method - Daniel, Barbara (My University, 2016)
#RhodesMustFall and #FeesMustFall are slogans that characterise the current state of protest, unrest, and crisis in South African higher education. Tension stems from disparate expectations and misalignment regarding the purposes, policies and functional processes of education, as well as the needs of students. Providing relevant education requires a dynamic and socially-referenced curriculum, including the delivery of teaching and learning (Van Rooyen, 2016). This exploratory research investigates how the tools and activities of the Flipped Classroom can contribute to an active learning environment based on student-centred learning, at a private higher education institution. This mode of education delivery, with its element of blended learning, has potential for redressing some of the negative effects of hidebound education traditions and colonisation. It does so by promoting a milieu wherein students are encouraged in self-reliance and self-determination, in keeping with the stated desires of students (Kamanzi, 2016a). Recommendations are also made for informing best practice in a B Ed (Foundation Phase) Programme
Keywords: Flipped classroom; South African higher education; Active learning; Private higher education